LRRK2 Inhibition by PF06447475 Antagonist Modulates Early Neuronal Damage after Spinal Cord Trauma - Alessia Filippone; Deborah Mannino; Laura Cucinotta; Irene Paterniti; Emanuela Esposito; Michela Campolo (MDPI AG, 2022)
Spinal cord injury (SCI) is a devastating event followed by neurodegeneration, activation of the inflammatory cascade, and immune system. The leucine-rich-repeat kinase 2 (LRRK2) is a gene associated with Parkinson's disease (PD), moreover, its kinase activity was found to be upregulated after instigated inflammation of the central nervous system (CNS). Here, we aimed to investigate the PF06447475 (abbreviated as PF-475) role as a pharmacological LRRK2 antagonist by counteracting pathological consequences of spinal cord trauma. The in vivo model of SCI was induced by extradural compression of the spinal cord, then mice were treated with PF0-475 (2.5-5 and 10 mg/kg i.p) 1 and 6 h after SCI. We found that PF-475 treatments at the higher doses (5 and 10 mg/kg) showed a great ability to significantly reduce the degree of spinal cord tissue injury, glycogen accumulation, and demyelination of neurons associated with trauma. Furthermore, oxidative stress and cytokines expression levels, including interleukins (IL-1, IL-6, IL-10, and 12), interferon-γ (IFN-γ), and tumor necrosis factor-α (TNF-α), secreted and released after trauma were decreased by LRRK2 antagonist treatments. Our results suggest that the correlations between LRRK2 and inflammation of the CNS exist and that LRRK2 activity targeting could have direct effects on the intervention of neuroinflammatory disorders.